Coping with [R]evolution in Online Games: Vulnerability and Resilience Responses to Change in MMO Game Expansions. Issue 2 (3rd April 2018) - Banks, Jaime; Martey, Rosa Mikeal
Abstract : Massively multiplayer online games (MMOs) often introduce new content and mechanics to increase player retention and enjoyment. Drawing on theories of socioecological risk response, this exploratory study examines players' in situ responses to these changes by analyzing patterns in public, in-game chat across 3 game expansions. Analysis reveals that a) change facilitates agenda setting in player chat, b) vulnerability and resilience expressions highlight tensions in player and game agencies, and c) increased semantic distance between the game and the "real" helps cope with game changes. In addition, sociotechnical affordances of MMO environments could be a mechanism for coping with change, more generally.